Targeted gene inactivation in Clostridium phytofermentans shows that cellulose degradation requires the family 9 hydrolase Cphy3367 - Tolonen, Andrew C (Blackwell Publishing Ltd, 2009)
Microbial cellulose degradation is a central part of the global carbon cycle and has great potential for the development of inexpensive, carbon-neutral biofuels from non-food crops. Clostridium phytofermentans has a repertoire of 108 putative glycoside hydrolases to break down cellulose and hemicellulose into sugars, which this organism then ferments primarily to ethanol. An understanding of cellulose degradation at the molecular level requires learning the different roles of these hydrolases. In this study, we show that interspecific conjugation with Escherichia coli can be used to transfer a plasmid into C. phytofermentans that has a resistance marker, an origin of replication that can be selectively lost, and a designed group II intron for efficient, targeted chromosomal insertions without selection. We applied these methods to disrupt the cphy3367 gene, which encodes the sole family 9 glycoside hydrolase (GH9) in the C. phytofermentans genome. The GH9-deficient strain grew normally on some carbon sources such as glucose, but had lost the ability to degrade cellulose. Although C. phytofermentans upregulates the expression of numerous enzymes to break down cellulose, this process thus relies upon a single, key hydrolase, Cphy3367.